Protective Signatures of Roselle (Hibiscus sabdariffa L.) Calyx Fractions against Staphylococcus aureus in Drosophila Infection Model - Firzan Nainu; M. Natsir Djide; Subehan Subehan; Sartini Sartini; Tri Puspita Roska; Emil Salim; Takayuki Kuraishi (Bogor Agricultural University, Indonesia, 2020)
The rise of antibiotic-resistant Staphylococcus aureus-related clinical cases is an alarming chronicle for global communities. This research was conducted to examine the antistaphylococcal effect of roselle (Hibiscus sabdariffa L.) calyx fractions in the Drosophila model. In the infection experiment, wild-type and immunodeficient Drosophila were pricked with S. aureus and subsequently subjected to fly survivorship and colony-forming assays, in the presence or absence of roselle calyx fractions. The Involvement of immune stimulation in the host antibacterial protection was assessed in vitro using cell-based luciferase reporter assay and in vivo using RT-qPCR analysis on adult flies. A declining rate of fly survivorship and augmentation of bacterial growth were observable in S. aureus-infected wild-type flies but subject to improvement in the presence of roselle calyx fractions. Cell-based analysis revealed the absence of host immune stimulation via Drosophila Toll pathway and roselle calyx fractions-treated immune-deficient flies lacking for components in the Toll pathway were protected from infection-induced early death phenotype and harbored reduced number of S. aureus colonies. Overall, our data confirmed the in vivo anti-staphylococcal activity of roselle calyx fractions in Drosophila infection model and such protective signature was devoid of host immune stimulation.